2019
DOI: 10.1080/19420862.2019.1583987
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α-3 ß-1’s central role in breast cancer, melanoma and glioblastoma cell aggregation revealed by antibodies with blocking activity

Abstract: Breast cancer, melanoma and glioblastoma cells undergo cell-mediated aggregation and aggregate coalescence in a transparent 3D Matrigel environment. Cells from normal tissue and non-tumorigenic cell lines do not exhibit these behaviors. Here, 266 monoclonal antibodies (mAbs) demonstrated to interact with a wide variety of membrane, secreted and matrix proteins, have been screened for their capacity to block these tumorigenic cell-specific behaviors in a 3D environment. Remarkably, only six of the 266 tested mA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 84 publications
0
13
0
Order By: Relevance
“…mAb NZ-1, described above, was affinity purified using a Protein G HP spin trap column (GE Healthcare, Cat.#28903134) and concentrated using an ultra-centrifugal filter (EMD Millipore, Cat.# UFC905024) [27]. The concentration was measured by a Nanodrop 1000 spectrophotometer (ThermoScientific) and 0.67 μg added to 4x10 4 F-NHDFs or CC-NHDFs in 200 μl of medium.…”
Section: Methodsmentioning
confidence: 99%
“…mAb NZ-1, described above, was affinity purified using a Protein G HP spin trap column (GE Healthcare, Cat.#28903134) and concentrated using an ultra-centrifugal filter (EMD Millipore, Cat.# UFC905024) [27]. The concentration was measured by a Nanodrop 1000 spectrophotometer (ThermoScientific) and 0.67 μg added to 4x10 4 F-NHDFs or CC-NHDFs in 200 μl of medium.…”
Section: Methodsmentioning
confidence: 99%
“…Further, pancreatic cancer patients with high expression of Integrin α3 had lower median survival than the comparable low expressing group [58]. Moreover, a recent study with blocking antibodies against integrin β1 or α3 in vitro revealed integrin α3β1 disruption of cell aggregation and aggregate coalescence in breast cancer, melanoma and glioblastoma cells [59]. Thus, CAF-regulated ECM remodeling in the TME enables CAFs and cancer cells to communicate with each other by exchanging signals that are mainly mediated through integrins, consequently supporting cancer progression.…”
Section: Communication Between Cafs and Cancer Cells Mediated By Imentioning
confidence: 99%
“…mAb concentration and purification were performed as previously described [14,15]. In brief, mAb supernatant was concentrated in VivaCell centrifugal filters with a 50 kDa cut off PLOS ONE (Satorius, Stonehouse, UK).…”
Section: Mab Concentration and Purificationmentioning
confidence: 99%
“…CD44, a transmembrane glycoprotein with a large extracellular domain [1][2][3][4][5], was originally identified as a receptor for the extracellular matrix molecule hyaluronic acid [6][7][8][9]. Subsequently, it was shown that CD44 played a role in a number of cellular processes related to adhesion and cell motility [2,[10][11][12][13], in some cases in the absence of hyaluronic acid [14,15]. CD44 is expressed in a variety of cell types [16][17][18], and has been shown to be up-regulated in stem cells [19][20][21][22] as well as select carcinomas [23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation